Telepathology consultation for frozen section diagnosis in China - Yingxin Huang; Yan Lei; Qi Wang; Dazhou Li; Lili Ma; Lili Guo; Minshan Tang; Guanglong Liu; Qianwen Yan; Lan Shen; Guihui Tong; Zhiliang Jing; et al. (BMC, 2018)
Abstract Background Telepathology (TP) provides remote pathology services for primary diagnosis practices, including intraoperative consultation of surgical pathology; it has not been widely implemented in China. In this study, the results of an implementation were reported, which lasted for two and a half years, and demonstrated the experience of the diagnosis of the intraoperative frozen sections by using TP consultation platform of Southern Medical University and Guangzhou Huayin Medical Laboratory Center (SMU-HUAYIN TP) in China. Methods The SMU-HUAYIN TP consultation platform connects 71 participating basic hospitals and 11 senior pathologists. Nanfang Hospital is a high-level hospital located in a large city in China. This retrospective study summarizes the experience and results of TP for frozen section diagnosis by comparing the data of the platform and Nanfang Hospital over a period of 2.5 years from January 2015 to June 2017. Results A total of 5233 cases were submitted to the platform, including 1019 cases in 2015, 2320 cases in 2016, and 1894 cases in 2017. The most common cases were breast (30.42%), followed by thyroid (29.05%) and gynecological (24.86%). Average turn-around time (TAT) of the cases from the platform in 2015 and 2016 was controlled within 30 min. In most TP cases (90.31%) and cases from Nanfang Hospital (86.14%), a definitive diagnosis was provided. The coincidence rate was 99.77% in the TP cases and 99.35% in the cases from Nanfang Hospital. The false positive and false negative rates of TP cases were 0.04 and 0.19%, respectively and no significant difference was found among different senior pathologists (P = 0.974, P = 0.989, P > 0.05). Similarly, there was no significant difference between TP cases and cases from Nanfang Hospital that were diagnosed by the same senior pathologist (P > 0.05). Conclusions Our results indicate that TP in frozen section diagnosis could improve patient care and solve the problem of unevenly distributed pathology resources in China. We believe that in the near future, TP in frozen section diagnosis will become an important component of telemedicine and will play a significant role in health care reform in China.